2004
DOI: 10.1023/b:bebm.0000035137.97552.ab
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monoamine Oxidase Gene Knockout on Dopamine Metabolism in Mouse Brain Structures

Abstract: Experiments were performed on knockout Tg8 mice lacking monoamine oxidase A gene that plays a major role in dopamine catabolism. The study by the method of high-performance liquid chromatography revealed considerable regional differences in the contents of dopamine and its metabolite dihydroxyphenylacetic acid in brain structures of these animals. Tg8 mice differed from the parent C3H/HeJ strain by low level of dihydroxyphenylacetic acid in the striatum, midbrain, hypothalamus, and hippocampus and high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The fact that the rise in DA EC elicited by the MA challenge injection was more persistent in MA-experienced vs. acutely treated animals (Figure 1) suggests that perhaps repeated drug experience lowered DA catabolism. As mentioned above, MA inhibits MAO (Fleckenstein et al, 2007) and the possibility exists that with repeated drug experience, this mechanism may contribute to this drug's capacity to promote higher DA EC levels, particularly within the NAC (Popova et al, 2004). In contrast to striatum, frontal cortical structures exhibit low DAT expression (Sesack et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the rise in DA EC elicited by the MA challenge injection was more persistent in MA-experienced vs. acutely treated animals (Figure 1) suggests that perhaps repeated drug experience lowered DA catabolism. As mentioned above, MA inhibits MAO (Fleckenstein et al, 2007) and the possibility exists that with repeated drug experience, this mechanism may contribute to this drug's capacity to promote higher DA EC levels, particularly within the NAC (Popova et al, 2004). In contrast to striatum, frontal cortical structures exhibit low DAT expression (Sesack et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory reported that GALP knockout mice developed normally with an onset of puberty similar to that of normal littermates (51). Numerous studies have demonstrated a lack of particular phenotypes in knockout mice as a result of hypothalamic compensatory mechanisms (52–57). Clearly, other hypothalamic systems are implicated in regulating the timing of the onset of puberty (58) and even mediating the effects of leptin to modulate the timing of the onset of puberty (59–61).…”
Section: Discussionmentioning
confidence: 99%
“…However, we recently found significant regional specificity of the effect of MAO A knockout on the metabolism of serotonin and catecholamines in different brain structures. The frontal cortex was more resistant to the absence of MAO A than others, including the hippocampus, midbrain, hypothalamus, striatum and amygdala [2,10].…”
mentioning
confidence: 88%
“…Recently, a strain of transgenic mice (Tg8) with an irreversibly destroyed gene of MAO A was obtained at Curie Institute [1]. Tg8 mice are deprived of MAO A and characterized by high levels of serotonin and noradrenalin and low concentrations of the final products of the oxidative deamination of serotonin and dopamine, 5-hydroxyindolacetic (5-HIAA) and 3,4-dihydroxyphenylacetic (DOPAA) acids [1,2]. In this work, we studied the effect of the genetic knockout of MAO A on the functional state and level of the mRNA of 5-çí 1Ä receptors in brain structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation